DAMPAK PANDEMI COVID-19 TERHADAP MANAJEMEN INDUSTRI PERBANKAN SYARIAH: ANALISIS KOMPARATIF - Mardhiyatur Rosita Ningsih; Muhammad Syarqim Mahfudz (POINT: Jurnal Ekonomi dan Manajemen, 2020)
Ministry of Health data shows the total confirmed cases of COVID-19 in Indonesia is 9,771 cases with a total of 784 deaths. Jakarta and West Java provinces are the regions with the highest number of Covid-19 cases. This is a challenge for the business world, including Sharia Banks, which based on Sharia banking Statistics data show that Jakarta is the region with the largest number of Sharia Bank branch offices in Indonesia. This study is a comparative analysis which aims to determine the impact of the Covid-19 pandemic on the banking industry on the side of the management of the Bank's operational strategies and Bank Intermediation Activities. The study used a sample of 5 Islamic Commercial Banks. The research sample was selected using purposive sampling technique. The results showed that in December to March 2020 all banks experienced turmoil in the intermediation function which tended to decline both from funding and fund raising. Meanwhile, in terms of Sharia Bank Strategy Management implementing a variety of policies including service restrictions through face-to-face, providing restructuring policies to affected customers and utilizing digital applications. Keywords: Covid-19, Islamic Banking Industry, Management